Body Resistance and Growth Performance of Broiler Fed Glucomannan Extracted from Amorphophallus onchophyllus Tuber - A. Perdinan; H. I. Wahyuni; N. Suthama (Tropical Animal Science Journal, 2019)
The purpose of the study was to examine the supplementation effects of glucomannan extracted from a porang tuber (GEPT) on body resistance and growth performance of broiler chickens. A total number of 160 one-day-old broiler chickens with the average body weight of 42.39±0.58 g was kept for 35 days. The study was arranged in a completely randomized design with 5 treatments and 4 replications (8 birds each). The dietary treatments were T0= basal ration, T1= basal ration with the addition of 0.05% GEPT, T2= basal ration with the addition of 0.1% GEPT, T3= basal ration with the addition of 0.15% GEPT, and T4= basal ration with the addition of 0.2% GEPT. Parameters measured were the population of lactic acid bacteria (LAB), Coliform count, relative weight of lymphoid organs (bursa fabricius and spleen), heterophils-lymphocytes (H/L) ratio, body weight gain, feed consumption, feed conversion ratio, and mortality. Data were subjected to analysis of variance (ANOVA) and continued with Duncan Multiple Range Test (DMRT) at 5% probability. The results showed that supplementation of the diets with GEPT significantly increased (P<0.05) LAB population, decreased (P<0.05) Coliform count in the jejunum and ileum, and H/L ratio, but did not affect the relative weight of lymphoid organs, and growth performance. In conclusion, diet added with 0.1% GEPT improved the balance of intestinal microflora and increased body resistance, without any negative effects on the lymphoid organs and growth performance of broiler chickens.